Sustainability of Participatory Technology Development & Transfer Approach for Sugarcane Farmers - Jeyarajan, Vasanthakumar (Journal of Extension Education, 2018)
Participatory Technology Development and Transfer (PTD & T) is an effective action research approach. It empowers all the stakeholders, especially the farmers who are many a time invisible. A PTD project was implemented for Sugarcane development in Tamil Nadu and the outcome was a mixture of success and failures. The paper presents the findings and asserts that the approach is sustainable.